Baseline Quantitative Hepatitis B Core Antibody Titer Is a Predictor for Hepatitis B Virus Infection Recurrence After Orthotopic Liver Transplantation - Lou, Bin; Ma, Guanghua; LV, Feifei; Yuan, Quan; Xu, Fanjie; Dong, Yuejiao; Lin, Sha; Tan, Yajun; Zhang, Jie; Chen, Yu (Frontiers in Immunology, 2021)
Objective Hepatitis B virus (HBV) reinfection is a serious complication that arise in patients who undergo hepatitis B virus related liver transplantation. We aimed to use biomarkers to evaluate the HBV reinfection in patients after orthotopic liver transplantation. Methods Seventy-nine patients who underwent liver transplantation between 2009 and 2015 were enrolled, and levels of biomarkers were analyzed at different time points. Cox regression and receiver operating characteristic (ROC) curves of different markers at baseline were used to analyze sustained hepatitis B surface antigen (HBsAg) loss. The Kaplan-Meier method was used to compare the levels of the biomarkers. Results Among the 79 patients, 42 sustained HBsAg loss with a median time of 65.2 months (12.0-114.5, IQR 19.5) after liver transplantation and 37 patients exhibited HBsAg recurrence with a median time of 8.8 (0.47-59.53, IQR 19.47) months. In the ROC curve analysis, at baseline, 4.25 log10 IU/mL qHBcAb and 2.82 log10 IU/mL qHBsAg showed the maximum Youden’s index values with area under the curves (AUCs) of 0.685and 0.651, respectively. The Kaplan-Meier method indicated that qHBsAg and quantitative antibody against hepatitis B core antigen (qHBcAb) levels in the two groups were significantly different (p = 0.031 and 0.006, respectively). Furthermore, the Cox regression model confirmed the predictive ability of qHBcAb at baseline (AUC = 0.685). Conclusion Lower pretransplantation qHBcAb is associated with HBV infection. The baseline concentration of qHBcAb is a promising predictor for the recurrence of HBV in patients undergoing liver transplantation and can be used to guide antiviral treatment for HBV infection.